2010
DOI: 10.1053/j.gastro.2010.04.045
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic and Protective Roles of MyD88 in Leukocytes and Epithelial Cells in Mouse Models of Inflammatory Bowel Disease

Abstract: Background & Aims-Toll-Like Receptors (TLR) are innate immune receptors involved in recognition of the intestinal micro-flora; they are expressed by numerous cell types in the intestine, including epithelial cells, myeloid cells and lymphocytes. Little is known about the relative contributions of TLR signaling in distinct cellular compartments to intestinal homeostasis. We aimed to define the roles of TLR signals in distinct cell types in the induction and regulation of chronic intestinal inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
91
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 41 publications
3
91
0
1
Order By: Relevance
“…Bone marrow transfer experiments showed that MyD88 signaling in hematopoietic cells mediated intestinal inflammation induced by H. hepaticus. Since both donor and acceptor mice in these experiments were RAG2-deficient, these results indicate that the proinflammatory effects of MyD88 in this colitis model reside in innate immune cells [44]. This is in accordance with the fact that colitis development in Il-10 -/-mice relies on MyD88 signaling and NF-κB activation in myeloid cells [22,23].…”
Section: Mechanisms Underlying the Dual Role Of Intestinal Nf-κb Actisupporting
confidence: 72%
See 2 more Smart Citations
“…Bone marrow transfer experiments showed that MyD88 signaling in hematopoietic cells mediated intestinal inflammation induced by H. hepaticus. Since both donor and acceptor mice in these experiments were RAG2-deficient, these results indicate that the proinflammatory effects of MyD88 in this colitis model reside in innate immune cells [44]. This is in accordance with the fact that colitis development in Il-10 -/-mice relies on MyD88 signaling and NF-κB activation in myeloid cells [22,23].…”
Section: Mechanisms Underlying the Dual Role Of Intestinal Nf-κb Actisupporting
confidence: 72%
“…These studies together suggest that the detrimental effects of NF-κB activation in the gut are, at least in part, mediated by MyD88-induced signaling in myeloid cells. In contrast, because irradiated Rag2 -/-/Myd88 +/+ mice reconstituted with Rag2 -/-/Myd88 -/-bone marrow cells did not display the spontaneous lethality observed in Rag2 -/-/ Myd88 -/-mice [44], the authors concluded that MyD88 signaling in epithelial cells is critical for host survival in the absence of adaptive immunity. Although reciprocal bone marrow transfer experiments could not be performed in this study, and although necessary experiments with IEC-specific MyD88 deficiency are missing, several indications support the hypothesis that MyD88 signaling in IECs indeed serves beneficial purposes in the gut immune system.…”
Section: Mechanisms Underlying the Dual Role Of Intestinal Nf-κb Actimentioning
confidence: 65%
See 1 more Smart Citation
“…Using a model of Helicobacter hepaticus-induced chronic inflammation, a recent study showed MyD88 signaling in leukocytes to be responsible for the phenotype (30). Also, using IL-10-deficient mice as a model of chronic T cell-dependent colitis, depletion of IKKβ in the myeloid compartment prolongs survival.…”
Section: Discussionmentioning
confidence: 99%
“…31 Epithelial signaling through the interleukin-1 and Toll-like receptor adapter molecule MyD88 as well as the MyD88 adaptor-like (Mal) was shown to promote epithelial integrity in models of enteric inflammation and infection. 2,[32][33][34][35] The phenotype of MyD88 ¡/¡ mice might at least in part be the result of a dysfunctional mucus layer since mucus production, antimicrobial peptide and RegIIIg expression, as well as luminal SIgA transport were all shown to require intact epithelial MyD88 signaling. 11,36 Accordingly, the thinner inner colonic mucus layer observed in germ-free mice was restored to the size of the one observed in conventional mice by administration of Toll-like receptor ligands.…”
mentioning
confidence: 99%